An Epidemiological Study of The Morbidity Pattern Among the Elderly Population in Ahmedabad, Gujarat - Rajshree Bhatt; Minal S Gadhvi; K N Sonaliya; Anand Solanki; Himanshu Nayak (Medsci Publications, 2011)
Background: Ageing is a part of the development sequences of entire life span, from prenatal growth to senescence. India is going to be having highest number of Elderly in world by year 2025.Morbidity among Elderly is a serious problem for health service utilization in India due to increase in elderly population. Aims & Objectives: To study the socio demographic profile and morbidity pattern among geriatric population of study area. Methodology: It was cross sectional community-based study done in Kalipinagar area of UHTC. All elders above age of 60 years are covered in survey on house visit. Data analysis was done using EPI-Info 6.4. Result: Total 218 elderly were surveyed (Male =74 & Female=144). Mean age of female was 50.31 & of male was 57.44. Among elderly surveyed, 92% were living in joint family. Nearly 34% of female were illiterate. 47.7% of elderly were earning with maximum wages between 1000- 2000 Rs/month. Among them majority were suffering from loco motor, visual & hypertension problem. Gender wise association was found significant when comparison was done between normotensive & pre hypertensive but not with hypertensive. Statistical significance was there between weights of male & female but no significance was there in BMI. Among tobacco users' gender wise difference was statistically significant. Pallor ness was common in both the gender.